Frida - Winter, Jonah; Juan, Ana (New York : Arthur A. Levine, 2002)
Illustrations and simple text help chronicle the life of artist Magdalena Carmen Frida Kahlo, discussing how she learned to paint, how painting saved her life, and why her paintings are so unique.
Wilson's Children, October 2010.
Notable/Best Books (A.L.A.), January 2003.
School Library Journal, March 2002.
Book Links (A.L.A.), October 2009.
Pub Weekly, December 2001.
Booklist, March 2002.
Keywords: Kahlo, Frida -- Juvenile literature; Kahlo, Frida; Kahlo, Frida; Painters -- Mexico -- Biography -- Juvenile literature; Artists; Artists -- Biography; Artists; Women -- Biography